Los medios didácticos “Visuales Simbólicos” y su influencia en el aprendizaje de la matemática en áreas poligonales de los alumnos del quinto grado de primaria en la I.E “José Carlos Mariátegui” del distrito de Rioja - Córdova Wajajay, Mariela Elizabeth (2012)
The present study has aimed to determine the influence of teaching aids visual symbolic in the learning of Mathematics in polygonal areas Fifth Grade students of Primary Schools in the district of Rioja. The type of research is explanatory, experimental level, pre-experimental design with pretest - posttest and one group, the sample consisted of 12 students. Data were collected using a test to measure the learning of mathematics in polygonal areas. The data were processed using the frequency distribution and the Student t distribution. In tne analysis of the results it was concluded that teaching aids "visual symbolic" significantly influence the Jearning of Mathematics in polygonal areas of fifth grade students of Primary Education in the Educational lnstitution Experimental José Carlos Mariátegui Rioja district in the 2011, with calculated t value (-5.09) lower than the tabulated value (-1.812) and with increased level of learning at home (83.33%) in the pretest to expected accomplishment (58.33) in the ppsttest.